Career decision-making resource priorities and the feasibility of tailoring career supports for people with multiple sclerosis: A latent profile analysis. - Bishop, Malachy; Li, Jian (Work, 2026)
Background: Multiple sclerosis (MS) is a prevalent, frequently progressive condition of the central nervous system that can significantly affect employment and career participation. Although researchers have extensively catalogued the factors that people with MS face in maintaining employment, the priorities of people working with MS in terms of career resources and information needs have not been extensively evaluated. Objective: We sought (a) to identify the types of career information and resources that employed or recently-employed people with MS prioritize, and (b) to assess the extent to which the need for these career resources may vary among identifiable subgroups. Method: Descriptive statistics and latent profile analysis (LPA) were applied to the responses of 376 iConquerMS members who were either employed (n = 279) or had been employed in the past 5 years (n = 97). Participants completed a web-based survey delivered through the iConquerMS web-based platform. Results: among seven career resource/information topics, the participants prioritized resources on the work and physical health relationship, employment rights and benefits, the work environment and employment communication, and mental health. The LPA failed to identify meaningful subgroups based on the types of career information and resources. Conclusion: This study provides important information on the career resource needs and priorities of individuals with MS. It contributes to the goal of providing timely and personally relevant information to ensure that working people with MS can make informed decisions about their employment and career future, maintain work when desired, and avoid premature employment termination or discontinuation.